2020
DOI: 10.1111/aor.13857
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique to produce tubular scaffolds based on collagen and elastin

Abstract: Diseases of the cardiovascular system are the leading cause of mortality in the world, responsible for an average of 17.9 million deaths per year. 1 The most expressive are the ischemic heart diseases which occur due to the obstruction of blood vessels. In this scenario, some of the main alternatives to restore blood flow are autologous grafts, balloon catheters, and metal stents. However, these treatments can cause several problems in the long run, such as inflammation, thrombosis, and neointimal hyperplasia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
1
13
0
5
Order By: Relevance
“…Since the blood vessels are predominantly fibrous, composed of collagen and elastin, the combination of these two polymers with polyurethane, was employed in the production of fibrous scaffolds. The obtained scaffold was hydrophilic and cell viability was proven for 72 h [ 51 ]. The natural ionic mucopolysaccharide with linear structure hyaluronic acid, possesses multiple active groups (carboxyl, hydroxyl and amino groups) that can be further chemically modified, expanding the applications of hyaluronic acid in the biomedical field [ 52 ].…”
Section: Engineering Implant Surfaces To Prevent Microbial Adhesion and Infectionmentioning
confidence: 99%
“…Since the blood vessels are predominantly fibrous, composed of collagen and elastin, the combination of these two polymers with polyurethane, was employed in the production of fibrous scaffolds. The obtained scaffold was hydrophilic and cell viability was proven for 72 h [ 51 ]. The natural ionic mucopolysaccharide with linear structure hyaluronic acid, possesses multiple active groups (carboxyl, hydroxyl and amino groups) that can be further chemically modified, expanding the applications of hyaluronic acid in the biomedical field [ 52 ].…”
Section: Engineering Implant Surfaces To Prevent Microbial Adhesion and Infectionmentioning
confidence: 99%
“…Unlike the well-known electrospinning method, RJS does not require high voltage, and protein denaturation is thus avoided 15 , 16 . We also previously showed that RJS can be used to produce tubular scaffolds with a diameter of less than 6 mm, which is advantageous for coronary applications 17 .…”
Section: Introductionmentioning
confidence: 96%
“…In our previous studies, we investigated the optimum parameters and intrinsic properties of PU-based scaffold production using RJS 17 – 19 . In the present study, we hypothesized that the addition of ECM-derived proteins to PU would improve the properties of RJS vascular graft scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Such nanoparticles coupled with conjugating moieties, such as peptides, aptamers, and small molecules, help to deliver drugs specifically to the target tissue, thereby preventing adverse effects of non-specific drug accumulation and toxicity [9,10]. More recently, nanoparticles have been used for fabricating multifunctional scaffolds for tissue engineering applications [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%